Towards a circular economy in food consumption: Food waste reduction practices as ethical work. (February 2022) - Lehtokunnas, Taru; Mattila, Malla; Närvänen, Elina; Mesiranta, Nina
This article explores the transition towards a circular economy in the context of household food waste practices. The research concerning the circular economy has mainly focused on engineering or the processes of production, manufacturing, business and industry. However, the transition towards a circular economy requires, in addition to new technologies, infrastructures and innovations, a societal change and a change in everyday practices. In this article, we address this by examining the everyday practices of food waste reduction in households as ethical work. We claim that the intertwined practices, institutions and policies of the circular economy create moral categories and responsibilities in everyday food consumption. Thus, the transition towards circular economy requires everyday ethical work carried out by consumers. However, our analysis also brings out some possible challenges related to this transition that has not yet been accomplished. Our research materials consist of 26 food waste diaries collected from Finnish households and participant observation in 4 leftover cooking workshops organized with the Finnish Martha organization. We adapt Michel Foucault's conception of ethics, focusing on the constitution of ethical subjectivity in food waste practices. Moreover, we utilize practice theoretical approach that has been widely used in food waste and sustainable consumption studies and connect it with Foucault's theory. Our results suggest that in order to understand the circular economy as a moral economy, it is crucial to note the moral complexity of everyday life that results from partly contradictory ethical sensitivities and practices.